Resistance of Bottle gourd ,Lagenaria Siceraria ('moline) standi. to vhitefly Bemisia tabaei (Genn. ) (Homoptera: Aleyrodidae). (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
See pdf Please